2022
DOI: 10.1155/2022/1234983
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Image Analysis of TVCDS in Infertile Patients with Polycystic Ovary Syndrome

Abstract: In order to analyze and examine the TVCDS images of infertile patients, this paper conducted an in-depth study based on the symptoms of polycystic ovary syndrome. Through the sample size estimation method, mathematical analysis, and other methods, the image examination of the polycystic ovary in TVCDS was successfully analyzed. 86 cases of infertile patients with PCS were divided into a control group treated with clomiphene alone and an observation group treated with clomiphene combined with TCM periodic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%